Effect of Tarantula cubensis alcohol extract and Capecitabin combine in Colorectal Cancer rats - Rahmi Canbar; Ozgur Ozdemir; Ahmet Levent Bas (Revista Científica, 2023)
Colon cancer (CRC) is one of the most common types of cancer in the world. In this study, the effects of Tarantula cubensis alcoholic extract (TCAE) and the Capecitabine in CRC were investigated. Wistar albino rats were divided into eight groups with 12 animals in each group: untreated healthy and CRC groups, healthy and CRC groups treated with TCAE or Capecitabine, and healthy and CRC groups treated with both TCAE and Capecitabine. Azoxymethane was used in all CRC groups. TCAE and Capecitabine were administered to the relevant groups starting in the 15th week. All rats were euthanized after 18 weeks, and tissue samples were collected. The mRNA levels of Bcl–2, Bax, and Cas–3 in the harvested tissues were determined using real–time PCR and histopathologically abnormal crypt foci (ACF) scores were determined. It was found that TCAE modulated the decreased Bax/Bcl–2 expression rate in the CC group, but had the opposite effect in healthy animals, which was significantly reduced compared to the healthy groups (P<0.05). In addition, this rate was significantly lower in Capecitabine administered groups compared to other groups, and a paradoxical effect was observed (P<0.05). No significant change was observed in Cas–3 expression levels in all groups (P>0.05). Importantly, single and combined use of TCAE and Capecitabine in rats with CRC significantly reduced ACF scores (P<0.05). It can be stated that TCAE can specifically modulate the decreased Bax/Bcl–2 ratio in animals with cancer, and the therapeutic efficacy of Capecitabine is achieved at a dose of 40 mg·kg-1.